Vanadium (V)-doped ZnFe layered double hydroxide for enhanced sonocatalytic degradation of pymetrozine - Keyikoglu, Ramazan; Khataee, Alireza; Lin, Hongjun; Orooji, Yasin (Elsevier Science Sa, 2022)
In ultrasonic (US) processes, the development of environmentally friendly, effective, low-cost, and durable catalysts is needed to degrade pollutants. Here, ZnFe layered double hydroxide (LDH) was doped with vanadium (V) for the sonocatalytic degradation of a pesticide pymetrozine. The resulting catalyst had an average thickness of 25 nm, a specific surface area of 125.38 m(2)/g, and a bandgap value of 2.20 eV. In 90 min ultrasonic treatment, V-doped ZnFe LDH had 73% pymetrozine removal efficiency, which was 32% more than that of undoped ZnFe LDH. The US/V-doped ZnFe LDH process had a strong synergistic effect (synergy factor 7.17), which resulted in 57% and 68% greater efficiencies than the US alone and V-doped ZnFe LDH alone, respectively. The role of radical oxygen species was confirmed by carrying out radical trapping experiments using different scavengers and electron paramagnetic resonance analyses. Due to its high stability, the catalyst had good reuse potential with only an 8% performance reduction after 5 reuse cycles. Besides, the leaching of heavy metals was insignificant owing to the high integrity of the catalyst as confirmed by SEM and X-ray diffraction analysis. According to the GC-MS analysis, pymetrozine was first transformed into cyclic compounds then into aliphatic compounds such as animated products and carboxylic acids.
Keywords: Layered double hydroxide; Pesticides; Pollutant removal; Ultrasonic water treatment; Vanadium doping